(untitled) (Prosiding dan Call Paper Widya Wiwaha, 2023)
This study aims to determine and analyze the effect of Profit Margin, Price Earning Ratio, Quick Ratio, Debt to Equity Ratio, and Inventory Turnover on Share Price in companies listed on the Indonesia Stock Exchange for the 2017-2021 period either simultaneously or partially. The data used is secondary data. By using the purposive sampling method, a total sample of 59 companies was obtained from 70 companies, then only 10 companies were selected. This study uses multiple linear regression analysis to see the effect of the independent variables on the dependent variable. The results of the study show that simultaneously, Re Profit Margin, Price Earning Ratio, Quick Ratio, Debt to Equity Ratio, and Inventory Turnover affect the stock price of companies that listed on the Indonesia Stock Exchange for the 2017-2021 period. But partially, only Operating Profit Margin and Debt to Equity have an effect on Stock Price. Meanwhile, the Price Earning Ratio, Quick Ratio, and Inventory Turnover have no effect on stock price for the 2017-2021 period.